On the Kinematics of Sea-Land Breeze and the Local Development of Convective Storms in the Metropolitan Area of Rio de Janeiro - Matola de Miranda Cardoso, Rodrigo; Karam, Hugo Abi; Soares de Azevedo, José Paulo (Anuário do Instituto de Geociências, 2024)
This work presents an analysis of the kinematic properties of the wind flow in the Metropolitan Area of Rio de Janeiro in the State of Rio de Janeiro, Brazil, using meteorological data from the aerodromes Santos Dumont, Galeão and Campo dos Afonsos, located in the city of Rio de Janeiro. The calculation of these kinematic quantities is based on the 'Linear Vector Point Function' (LVPF) method. The results indicate the main role of the circulation of the sea-land breeze, the effects of topography (by blockages, channeling and differential heating) and the urban breeze associated with the development of the Urban Boundary Layer in the local formation of convective rainstorms in the Metropolitan Area of Rio de Janeiro.